Analise da concordância entre instrumentos de avaliação do tempo de execução do Time-up and Go (TUG) em pessoas idosas - Alvarez, Ieda Fernanda (2021)
The quality of life of the elderly population is associated to the maintenance of functional capacity. Declines in functional capacity resulting from aging are related to falls in older adults. About 400,000 people die each year around the world after they have had fallen. When falls do not result in death or serious injuries, they can lead to dependency, decreased mobility, decision deficits and an increased risk of falls. There are different tests and scales used to identify changes in functional capacity in the elderly population. Among these tests, Timed-up and Go (TUG) stands out due to its standardization, validation and practicality. The total time to complete TUG has been used to assess the mobility and balance. However, the “gold standard” instrument for obtaining time during TUG execution is the manual stopwatch, which can influence on the data acquisition. The use of more robust instruments (inertial sensors and force platform) would allow for more accurate assessments of the functional capacity of the elderly population. Therefore, the objective of the present study is to assess an agreement between instruments to assess the time to perform the TUG in older adults. For this, the study included 30 samples from the force platform and 14 samples from the inertial sensors, obtained during the performance of the TUG by 5 older adults (66.2 ± 7.2 years). The agreement between measurements was analyzed using correlation tests, Intraclass Correlation Coefficients (ICC), and Bland-Altman graphs. The results revealed that there were positive associations between the times obtained from the stopwatch with the times obtained from the force platform (rs=0.97) and from the inertial sensors (r=0.90). The ICCs indicate an excellent reliability between the times obtained from the stopwatch with the times obtained from the force platform (ICC=0.987) and the inertial sensors (ICC=0.925). Finally, the Bland-Altman graphs showed agreement between the times obtained from the stopwatch with the times obtained from the force platform and inertial sensors. In conclusion, there is agreement between the stopwatch data with data from the force platform and the inertial sensors for the evaluation of the TUG in older adults.